2017
DOI: 10.3171/2016.7.jns16322
|View full text |Cite
|
Sign up to set email alerts
|

The force pyramid: a spatial analysis of force application during virtual reality brain tumor resection

Abstract: OBJECTIVE Virtual reality simulators allow development of novel methods to analyze neurosurgical performance. The concept of a force pyramid is introduced as a Tier 3 metric with the ability to provide visual and spatial analysis of 3D force application by any instrument used during simulated tumor resection. This study was designed to answer 3 questions: 1) Do study groups have distinct force pyramids? 2) Do handedness and ergonomics influence force pyramid structure? 3) Are force pyramids dependent on the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 24 publications
0
46
0
1
Order By: Relevance
“…To our knowledge, this is the first study that obtained force data from neurosurgical patients during surgery. Although other studies 12,14,15,22,27 have used surgical models or simulators in assessing force data, none of these represented an ideal, realistic surgical scenario that includes not only the physical properties but also the psychological stress related to the performance of surgery. The range of forces in this study was different from those previously reported using cadaver brain.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that obtained force data from neurosurgical patients during surgery. Although other studies 12,14,15,22,27 have used surgical models or simulators in assessing force data, none of these represented an ideal, realistic surgical scenario that includes not only the physical properties but also the psychological stress related to the performance of surgery. The range of forces in this study was different from those previously reported using cadaver brain.…”
Section: Discussionmentioning
confidence: 99%
“…[39] However these systems do not allow for an assessment of quantitative instrument force application and instrument movements in a 3D operative environment nor provide verbal, visual and auditory feedback which may enhance the learning opportunities for the trainee. [10,21,40]…”
Section: Benefits Of the Virtual Operative Assistantmentioning
confidence: 99%
“…Whether these parametric features are the most appropriate or other metrics such as the force pyramid or automaticity will be more useful needs to be accessed. [17][18][19][20] Second, a simulated aspirator was utilized in the dominant hand which is not representative of the bimanual psychomotor skills and multiple instruments employed during patient tumor resections. Previous studies have demonstrated differences in ergonomics between right and left handed operators and this issue was not addressed in this investigation and deserves further study.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Previous studies have demonstrated differences in ergonomics between right and left handed operators and this issue was not addressed in this investigation and deserves further study. 17 Third, the different visual and haptic complexities of simulated tumors utilized and task duration may not adequately discriminate operator performance. More complex and realistic tumor scenarios with simulated bleeding involving use of bimanual instruments are being studied using classifiers which may be more useful.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
See 1 more Smart Citation